The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0103-64402009000200009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of casting atmosphere on the shear bond strength of a ceramic to Ni-Cr and Ni-Cr-Be alloys

Abstract: The success of metal-ceramic restorations depends on an optimal bond between metal and ceramic. This study evaluated the effect of 3 casting atmospheres on the metal-ceramic bond strength (MCBS) of 2 Ni-Cr alloys, with beryllium (Fit Cast V) and without beryllium (Fit Cast SB). Sixty acrylic resin patterns (8 mm long and 5 mm diameter) were obtained using a fluorocarbon resin matrix. Wax was used to refine the surface of acrylic resin patterns that were invested and cast in an induction casting machine under n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(36 reference statements)
1
1
0
3
Order By: Relevance
“…The sample size for the metal-ceramic bond strength was based on the study of Farzin et al 29 , that showed a minimally significant difference of 8.23 and a standard deviation of 6.02, which led to n = 9/group to ensure a power of 80% (α = 0.05; β = 0.2). However, the sample size was increased to 10, consistent with that of previous study by the research group 30 .…”
Section: Bondsupporting
confidence: 69%
“…The sample size for the metal-ceramic bond strength was based on the study of Farzin et al 29 , that showed a minimally significant difference of 8.23 and a standard deviation of 6.02, which led to n = 9/group to ensure a power of 80% (α = 0.05; β = 0.2). However, the sample size was increased to 10, consistent with that of previous study by the research group 30 .…”
Section: Bondsupporting
confidence: 69%
“…Some authors stated that there is no methodology capable of measuring only shear forces along the metal-porcelain interface. 2,20,21 Hammad and Talic 20 carried out a critical analysis of tests used for metal-ceramic systems. These authors stated that shear tests with a flat interface mostly direct the tension to the interface and does not evaluate the elasticity modulus of the metal as in flexural tests.…”
Section: Discussionmentioning
confidence: 99%
“…A utilização do berílio em ligas de Ni-Cr, outrora muito empregado por favorecer a fusibilidade dessas ligas e aumentar a resistência de união metalocerâmica (MACKERT; PARRY; FAIRHURST, 1986;BEZZON et al, 1998) foi questionada, principalmente por sua presença predispor a liga metálica à maior corrosão em meio bucal (WATAHA; MESSER, 2004). Além disso, outros estudos comprovaram que a adição desse elemento químico às ligas odontológicas não aumenta a resistência de união metalocerâmica (BEZZON et al, 2001;PAGNANO et al, 2009).…”
Section: Introductionunclassified